2002
DOI: 10.1021/jp013587s
|View full text |Cite
|
Sign up to set email alerts
|

Core Ionization Energies, Mean Dipole Moment Derivatives, and Simple Potential Models for B, N, O, F, P, Cl, and Br Atoms in Molecules

Abstract: Simple potential models relating experimental 1s electron ionization energies for B, N (sp and sp3 hybrids), O, and F atoms; 1s and 2p ionization energies for P atoms; and 2s and 2p ionization energies for Cl atoms as a function of their atomic mean dipole moment derivatives determined from experimental gas phase infrared fundamental band intensities are reported. Potential models using theoretical Koopmans' energies and generalized atomic polar tensor (GAPT) charges are found to form even more precise models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…[81][82][83][84] Siegbahn et al's simple potential model 85 corrected for relaxation energy of the 1s core ionization energy of the carbon atom is given by (12) where E C,1s is the carbon 1s core ionization energy, q A and q C are atomic charges, R AC is the internuclear distance between the A and C atoms and E relax is the relaxation energy for the ionization process. The first two terms in this equation can be derived from purely electrostatic considerations 85 or from quantum mechanical argument.…”
Section: Gapt Charges and Core Ionization Energiesmentioning
confidence: 99%
“…[81][82][83][84] Siegbahn et al's simple potential model 85 corrected for relaxation energy of the 1s core ionization energy of the carbon atom is given by (12) where E C,1s is the carbon 1s core ionization energy, q A and q C are atomic charges, R AC is the internuclear distance between the A and C atoms and E relax is the relaxation energy for the ionization process. The first two terms in this equation can be derived from purely electrostatic considerations 85 or from quantum mechanical argument.…”
Section: Gapt Charges and Core Ionization Energiesmentioning
confidence: 99%
“…This is more conveniently explained using the GAPT charges. Siegbahn and co-workers 11 have shown that Koopmans' energy can be calculated using a simple potential model represented by the equation: 17,18 Evidently, the formation energy of the hydrogen bond and GAPT oxygen charges are not highly correlated because the electrostatic potential at the oxygen atom contributed by the neighboring atoms is also important in the hydrogen bonding process. In other words an approaching donor molecule is influenced not only by the charge of the acceptor oxygen atom but also by the charges on the other atoms in the molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore the GAPT charges have been shown to be related to atomic electrostatic potentials by Siegbahn's simple potential model. 17,18 These relationships suggest the use of Koopmans' energies for core electrons as QSAR descriptors in activity problems for which the H-bonding phenomenon is important.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Theoretical models based on Koopmans' energies and mean dipole-moment derivatives calculated by quantum chemical procedures have also been reported for all of the above atoms and for the 1s, 2s, 2p, 3s, 3p, and 3d electrons of the bromine atom. 3 Siegbahn introduced the simple potential model for core electron ionization energies using atomic point charges. The fact that mean dipole-moment derivatives work so well in these models leads to the proposal that these derivatives can be identified with atomic charges.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, they have been shown to be related [1][2][3] by a simple potential model, first proposed by Siegbahn,4 in which the ionization energies are a function of atomic charges and internuclear distances. In terms of mean dipole-moment derivatives, p j R and p j , of the nucleus being ionized, R, and other nuclei in the molecule, where E R,core represents the ionization energy of a core electron of the Rth nucleus.…”
Section: Introductionmentioning
confidence: 99%